CBIO-03. ATRX LOSS IN GLIOMA RESULTS IN EPIGENETIC DYSREGULATION OF CELL CYCLE PHASE TRANSITION. (9th November 2020) - Mullan, Brendan; Qin, Tingting; Siada, Ruby; Ravindran, Ramya; Thomas, Chase; Harris, Micah; Muruganand, Ashwat; Pyaram, Kalyani; Miklja, Zachary; Reiber, Mary; Garcia, Taylor; Tran, Dustin; et al.
Abstract: Gliomas are a leading cause of cancer mortality in children and adults, and new targeted therapies are desperately needed. ATRX is a chromatin remodeling protein that is recurrently mutated in H3F3A -mutant pediatric glioblastoma (GBM) and IDH -mutant grade 2/3 adult glioma. We previously showed that loss of ATRX in glioma results in tumor growth and additional tumor mutations. However, the mechanism driving these phenotypes has not been fully established. We found that in ChIP-Seq/ChIP-qPCR of mouse neuronal precursor cells (NPCs) and GBM cells with isogenic ATRX loss, ATRX binds regulatory elements for cell cycle phase transition gene sets, and ATRX loss subsequently results in reduced expression. Furthermore, human GBM cells with ATRX knock-out demonstrate higher rates of cells in S and G2/M phases, with clusters of cells demonstrating reduced expression of cell cycle regulatory gene sets by single-cell sequencing (scSeq) analysis. In human and mouse GBM in vitro models, ATRX-deficient cells exhibit a seven-fold increase in mitotic index at 16 hours after sub-lethal radiation and enhanced activation of the master cell cycle regulator ATM with radiation. Treatment of ATRX-deficient gliomas with ATM inhibitors results in a selective increase in dysfunctional cell cycling and increased radio-sensitization in ATRX-deficient glioma cells. Using an ATM-luciferase reporter in orthotopically-implanted human GBM cells, both AZD0156 and AZD1390 demonstrate in vivo pathway inhibition. Mice intra-cranially implanted with ATRX-deficient GBM cells demonstrate a doubling of median survival compared to radiated controls (p=0.0018) when treated with AZD0156 combined with radiation; this is not seen in ATRX-sufficient models. This study demonstrates that ATRX-deficient high-grade gliomas display epigenetic dysregulation of cell cycle phase transitions, which opens a new window for therapies targeting this unique phenotype.